Study of 2-Amino-2-Methyl-1-Propanol Effect on Corrosion of Boiler Low Carbon Steel Pipes in Presence of Sodium Sulfite (Thamar University Journal of Natural & Applied Sciences, 2023)
This paper studies the effect of 2-Amino-2-mthyl-1-propanol (C3H11NO) on corrosion behavior of boiler steel pipes with low carbon content at sodium sulfite (Na2SO3) in the additive mixtures form as oxygen scavengers in the boiler feed water. Experiments were done at temperatures (100 - 150) ºC and pressures (5 - 9) × 101.3 KN/m² in cylinder autoclave with 7.4 ppm dissolved oxygen in used water, then the corrosion rate is measured by weight loss technique and the concentration of dissolved oxygen in feed water was determined before and after the experiment by Winkler method (Titration). This analysis can provide valuable information for mixture scavengers and corrosion behavior on boiler steel pipes with range of used temperature and pressure. The better ratios found is 60 ppm for every one of amine and sulfite, with the best result in decreasing corrosion rate in acceptable way. The above mentioned ratio is optimal and recommended. This opens up the field for formulation synergetic packages of additives as O2 scavengers. Keywords: Oxygen Scavenger, Na2SO3, C3H11NO, Boiler Steel Pipes, NA-Sulfite & 2-Amino-2-mthyl-1-propanor Additive Package